Analisis Miskonsepsi Muatan IPA Materi Sistem Peredaran Darah Manusia menggunakan Asesmen Peta Konsep di Sekolah Dasar - Aulia Itsna Fajriyanti; Ika Candra Sayekti (Jurnal Penelitian Pendidikan IPA, 2022)
Understanding of science concepts is important so that students are able to describe and relate a concept to other concepts. The reality is that students often do not understand science concepts in depth. This study aims to identify the misconceptions that occur in the content of IPA, the sub-concept of the human circulatory system with a concept map assessment. The method used is descriptive qualitative. This study uses tests and interviews as data collection techniques. This research was conducted at SD Negeri Manahan with the research subject being fifth grade students consisting of 25 students. The research guidelines were in the form of a concept map making test and interviews. The results showed that there were still students who had misconceptions about the human circulatory system, namely the value in the low category of 48% of students, medium category of 40% of students, and high category of 12% of students. The biggest misunderstanding occurs in the concept of the function and name of each organ in the human circulatory system.